Attitude, Intent and Different Aspects of Marriage in University Students: A Path Analysis. Issue 3 (3rd April 2022) - Nejatian, Mahbobeh; Alami, Ali; Tehrani, Hadi; Jahantigh, Hanieh; Jafari, Alireza
ABSTRACT: This cross-sectional study aimed to determine the attitude, intention and aspects of marriage among students. There was a significant relationship between gender and general attitude toward marriage and, mean score of male students' attitude toward marriage was higher ( P < .05). Based on the results of path analysis, sub-scales of general attitude toward marriage and Aspects of Marriage, explained 40% of the variance for the Intent to Marry. The results showed that students' attitude toward marriage was moderate and their marriage intention was not high. According to the results, it is necessary that implemented the training courses to change attitudes and create realistic expectations about marriage in the students.